Cell division cycle 20 overexpression predicts poor prognosis for patients with lung adenocarcinoma. Issue 3 (March 2017) - Shi, Run; Sun, Qi; Sun, Jing; Wang, Xin; Xia, Wenjie; Dong, Gaochao; Wang, Anpeng; Jiang, Feng; Xu, Lin
The cell division cycle 20, a key component of spindle assembly checkpoint, is an essential activator of the anaphase-promoting complex. Aberrant expression of cell division cycle 20 has been detected in various human cancers. However, its clinical significance has never been deeply investigated in non-small-cell lung cancer. By analyzing The Cancer Genome Atlas database and using some certain online databases, we validated overexpression of cell division cycle 20 in both messenger RNA and protein levels, explored its clinical significance, and evaluated the prognostic role of cell division cycle 20 in non-small-cell lung cancer. Cell division cycle 20 expression was significantly correlated with sex (p = 0.003), histological classification (p < 0.0001), and tumor size (p = 0.0116) in non-small-cell lung cancer patients. In lung adenocarcinoma patients, overexpression of cell division cycle 20 was significantly associated with bigger primary tumor size (p = 0.0023), higher MKI67 level (r = 0.7618, p < 0.0001), higher DNA ploidy level (p < 0.0001), and poor prognosis (hazard ratio = 2.39, confidence interval: 1.87–3.05, p < 0.0001). However, in lung squamous cell carcinoma patients, no significant association of cell division cycle 20 expression was observed with any clinical parameter or prognosis. Overexpression of cell division cycle 20 is associated with poor prognosis in lung adenocarcinoma patients, and its overexpression can also be used to identify high-risk groups. In conclusion, cell division cycle 20 might serve as a potential biomarker for lung adenocarcinoma patients.